The dogs of winter - Pyron, Bobbie (Arthur A. Levine Books/Scholastic, 2012)
Brought to Moscow in 1990s Russia by his mother's abusive boyfriend, five-year-old Mishka is forced by a gang of homeless children to lie and steal until he finds comfort and love with a pack of dogs. Includes historical note.